El civilizador. Historia de la humanidad por sus grandes hombres - Lamartine, Alphonse Marie Louis 1790-1869
Contiene: Homero, Juana de Arco, Bernardo de Palissy, Cristóbal Colón, Cicerón, Guttemberg, Eloisa, Fenelón, Sócrates, Horacio Nelson, Bustan, JAcquard, Oliveros Cromwell, Guillermo Tell, Bossuet, Miltón, Antar, MAdama de Sévigné